Organizations and Communication Technology - Fulk Janet; Steinfield Charles (Sage Publications, 1990)
Preface, Theorizing About Information Technology in Organizations, The Theory Imperative, Two Views of Information Technology and Tasks and Organizations, Conceptualizing Information Technology as Organization and Vice Versa, Individual Interactions with Information Technology in the Organizational Context, Understanding Managers' Media Choices: A Symbolic Interactionist Perspective, Opportunities for Strategic Information Manipulation Through New Information Technology, A Social Influence Model of Technology Use, Information Technology and Collective Behaviors, Communication Networks and New Media in Organizations, Understanding the Use of Group Decision Support Systems: The Theory of Adaptive Structuration, Toward a ''Critical Mass Theory of Interactive Media, Information Technology and Organizational Design, The Substitution of Communication Technologies for Organizational Structure in Research and Development, Telecommunications and Organizational Choice, Author and Subject Index.
Preface, Theorizing About Information Technology in Organizations, The Theory Imperative, Two Views of Information Technology and Tasks and Organizations, Conceptualizing Information Technology as Organization and Vice Versa, Individual Interactions with Information Technology in the Organizational Context, Understanding Managers' Media Choices: A Symbolic Interactionist Perspective, Opportunities for Strategic Information Manipulation Through New Information Technology, A Social Influence Model of Technology Use, Information Technology and Collective Behaviors, Communication Networks and New Media in Organizations, Understanding the Use of Group Decision Support Systems: The Theory of Adaptive Structuration, Toward a ''Critical Mass Theory of Interactive Media, Information Technology and Organizational Design, The Substitution of Communication Technologies for Organizational Structure in Research and Development, Telecommunications and Organizational Choice, Author and Subject Index.